Connection and Community - Vochatzer, Stefanie (Creative Approaches to Climate and Peace Education. An Educationr’s Guide to Using Storytelling and Art)

Validation of the maximal cardiopulmonary exercise test in adolescents with major depressive disorder and comparison of cardiorespiratory fitness with sex- and age-related control values - Wenzel, Charlotte; Bongers, Bart Chateau; Schlagheck, Marit Lea; Reis, Daniela; Reinhard, Franziska; Schmidt, Peter; Bernitzki, Stefan; Oberste, Max; Wunram, Heidrun Lioba; Zimmer, Philipp; Fricke, Oliver (European Journal of Pediatrics)
Abstract Endurance training has been shown to be effective in treating adolescents with major depressive disorder (MDD). To integrate endurance training into the therapeutic setting and the adolescents' daily lives, the current performance status of the adolescents should be accurately assessed. This study aims to examine adolescents with MDD concerning exhaustion criteria during a cardiopulmonary exercise test (CPET), as well as to compare the values obtained thereon with sex- and age-related control values. The study included a retrospective examination of exhaustion criteria ((i) oxygen consumption (V̇O 2 ) plateau, (ii) peak respiratory exchange ratio (RER peak ) > 1.0, (iii) peak heart rate (HR peak ) ≥ 95% of the age-predicted maximal HR, and (iv) peak blood lactate concentration (BLC peak ) > 8.0 mmol⋅L −1 ) during a graded CPET on a cycle ergometer in adolescents with MDD (n = 57). Subsequently, maximal V̇O 2 , peak minute ventilation, V̇O 2 at the first ventilatory threshold, and peak work rate of participants who met at least two of four criteria were compared with published control values using an independent-sample t-test. Thirty-three percent of the total population achieved a V̇O 2 plateau and 75% a RER peak > 1.0. The HR and BLC criteria were met by 19% and 22%, respectively. T-test results revealed significant differences between adolescents with MDD and control values for all outcomes. Adolescents with MDD achieved between 56% and 83% of control values. Conclusions : The study shows that compared with control values, fewer adolescents with MDD achieve the exhaustion criteria on a CPET and adolescents with MDD have significantly lower cardiorespiratory fitness. Clinical trial registration : No. U1111-1145–1854. What is Known: • It is already known that endurance training has a positive effect on depressive symptoms. What is New: • A relevant proportion of adolescents with major depressive disorder do not achieve their V̇O2max during a graded cardiopulmonary exercise test. • Adolescents with major depressive disorder have significantly lower cardiorespiratory fitness compared to sex- and age-related control values.

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian Gabriel; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)

Sprachlichkeit des Geschichtslernens. Fachliche Grundlagen, Sprachgebrauch und Ansätze fachintegrierter Spracharbeit - Hartung, Olaf (Beiträge zur Lehrerinnen- und Lehrerbildung)

Mediale und digitale Darstellungen des Immateriellen Kulturerbes während der Coronapandemie in Praxis und Forschung - Leineweber, Jonas (Heimat in Europa - Themen der BHU 2021)
Fragen der medialen Darstellung des Immateriellen Kulturerbes sind zwar nicht neu, haben durch die Coronapandemie aber enorm an Bedeutung gewonnen. Dabei werden nicht nur die Trägergruppen und Akteurinnen und Akteure, sondern auch die sich mit dem Immateriellen Kulturerbe auseinandersetzenden Forschungsprojekte vor Herausforderungen gestellt. Wie können Untersuchungen ermöglicht werden, wenn der Zugang zum Feld durch zahlreiche Einschränkungen erschwert oder aufgrund von Absagen und Ausfällen nicht möglich ist? Wie lassen sich die Auswirkungen der Coronapandemie wiederum in Forschungsvorhaben einbinden und zum Gegenstand wissenschaftlicher Auseinandersetzungen machen? Und schließlich: Wie können die Forschungsergebnisse niederschwellig vermittelt und in Interaktion mit den Trägergruppen diskutiert und perspektiviert werden, wenn klassische Informationsangebote wie Vortrags- und Workshopformate pandemiebedingt nicht stattfinden können? Mit diesen Fragen sah sich das seit 2016 laufende Forschungsprojekt „Tradition im Wandel – Das Schützenwesen in Westfalen als Immaterielles Kulturerbe“ während der Coronapandemie konfrontiert.
Keywords: Immaterielles Kulturerbe; Bräuche; Rituale; Feste; Medien; digital

Methodical approach for the design and dimensioning of mechanical clinched assemblies - Zirngibl, Christoph; Martin, Sven; Steinfelder, Christian; Schleich, Benjamin; Tröster, Thomas; Brosius, Alexander; Wartzack, Sandro (Materials Research Proceedings)
The focus towards multi-material and lightweight assemblies, driven by legal requirements on reducing emissions and energy consumptions, reveals important drawbacks and disadvantages of established joining processes, such as welding. In this context, mechanical joining technologies, such as clinching, are becoming more and more relevant especially in the automotive industry. However, the availability of only few standards and almost none systematic design methods causes a still very time- and cost-intensive assembly development process considering mainly expert knowledge and a considerable amount of experimental studies. Motivated by this, the presented work introduces a novel approach for the methodical design and dimensioning of mechanically clinched assemblies. Therefore, the utilization of regression models, such as machine learning algorithms, combined with manufacturing knowledge ensures a reliable estimation of individual clinched joint characteristics. In addition, the implementation of an engineering workbench enables the following data-driven and knowledge-based generation of high-quality initial assembly designs already in early product development phases. In a subsequent analysis and adjustment, these designs are being improved while guaranteeing joining safety and loading conformity. The presented results indicate that the methodological approach can pave the way to a more systematic design process of mechanical joining assemblies, which can significantly shorten the required number of iteration loops and therefore the product development time.
Keywords: Joining; Structural Analysis; Machine Learning

Experimental investigation of the cause and effect relationships between the joint and the component during clinching - Steinfelder, Christian; Brosius, Alexander (Materials Research Proceedings)
The combination of the mechanical properties of a clinched joint and of the material surrounding the joint determine the resulting properties of the component and joint. The cause and effect relationships between the joint and the joint environment offers the possibility of a specific modification through an adaptation in the design process. In order to identify these cause and effect relationships and resulting interactions experimentally, numerous of experiments are required. In this publication, a concept for the automated manufacturing of head tensile test and shear tensile test specimens – from cutting to clinching – by using a punch laser machine is presented. Based on a full-factorial experimental design, the parameters change of the properties of the joint environment by beading and change of the punch displacement are addressed. The influence on the properties of the clinched specimen is evaluated based on the variables Stiffness, force at the beginning of yielding and maximum force at head tensile loading and shear tensile loading. In addition, the geometric quality parameters of neck thickness, interlock and bottom thickness are evaluated. The relationships can be used to apply uniform loads to joints in joined structures to counteract oversizing.
Keywords: Sheet Metal; Joining; Stiffness

Das Eigene und das Fremde - Einblicke in schulnahe Curriculumarbeit im Bildungsgang Industriekaufmann/-frau zur Konstruktion von interdisziplinärer Verständigung zwischen gewerblich-technischen und kaufmännischen Bildungsgängen. - Koppius, Sebastian Niklas

Emergent communication enhances foraging behavior in evolved swarms controlled by spiking neural networks - Jimenez Romero, Cristian; Yegenoglu, Alper; Pérez Martín, Aarón; Diaz-Pier, Sandra; Morrison, Abigail (Swarm Intelligence)
Abstract Social insects such as ants and termites communicate via pheromones which allow them to coordinate their activity and solve complex tasks as a swarm, e.g. foraging for food or finding their way back to the nest. This behavior was shaped through evolutionary processes over millions of years. In computational models, self-coordination in swarms has been implemented using probabilistic or pre-defined simple action rules to shape the decision of each agent and the collective behavior. However, manual tuned decision rules may limit the emergent behavior of the swarm. In this work we investigate the emergence of self-coordination and communication in evolved swarms without defining any explicit rule. For this purpose, we evolve a swarm of agents representing an ant colony. We use an evolutionary algorithm to optimize a spiking neural network (SNN) which serves as an artificial brain to control the behavior of each agent. The goal of the evolved colony is to find optimal ways to forage for food and return it to the nest in the shortest amount of time. In the evolutionary phase, the ants are able to learn to collaborate by depositing pheromone near food piles and near the nest to guide other ants. The pheromone usage is not manually encoded into the network; instead, this behavior is established through the optimization procedure. We observe that pheromone-based communication enables the ants to perform better in comparison to colonies where communication via pheromone did not emerge. Furthermore, we assess the foraging performance of the ant colonies by comparing the SNN-based model to a multi-agent rule-based system. Our results show that the SNN-based model can efficiently complete the foraging task in a short amount of time. Our approach illustrates that even in the absence of pre-defined rules, self-coordination via pheromone emerges as a result of the network optimization. This work serves as a proof of concept for the possibility of creating complex applications utilizing SNNs as underlying architectures for multi-agent interactions where communication and self-coordination is desired.

(Photo-)electrochemical reactions on semiconductor surfaces, part B: III-V surfaces–atomic and electronic structure - Hajduk, Andreas; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Guidat, Margot; Löw, Mario; Ullmann, Fabian; Moritz, Dominik C.; Hofmann, Jan P.; Krischok, Stefan; Runge, Erich; Schmidt, Wolf Gero; Jaegermann, Wolfram; et al. (Encyclopedia of Solid-Liquid Interfaces)

Socialist AI? Societal Use, Economic Implementation, and the Tensions of Applied Computer Science in Late Socialist GDR - Schmitt, Martin (IEEE Annals of the History of Computing)
Keywords: Sozialismus; Schachcomputer; Deutschland {<}DDR{>}; KI; Schach; Spätsozialismus; 1980er-Jahre

Chemoenzymatic Synthesis of Chiral Building Blocks Based on the Kinetic Resolution of Glycerol‐Derived Cyclic Carbonates - Terazzi, Constanza; Spannenberg, Anke; von Langermann, Jan; Werner, Thomas (ChemCatChem)
Abstract The biocatalytic kinetic resolution of cyclic carbonates derived from glycerol is reported. A selection of 26 esterases and lipases was tested for the asymmetric hydrolysis of the model substrate (epichlorohydrin carbonate) in aqueous medium. Among them, Pig Liver Esterase and Novozym® 435 showed the best selectivity with E =38 and 49, respectively. Both enzymes were employed for the conversion of 12 glycerol derivatives under optimized conditions. The resolution of halogenated carbonates afforded the unconverted enantiomer in up to >99 : 1 er . Furthermore, Novozym® 435 was successfully recycled 10 times without significant loss of activity. Upscaling and isolation of the chiral carbonate was also demonstrated. Subsequent conversion of this chiral building block allowed the direct one‐pot synthesis of ( S )‐Guaifenesin, ( S )‐Mephenesin and ( S )‐Chlorphenesin in up to 89 % yield and 94 : 6 er .
Keywords: T1; T4; CSSD

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Emission enhancement of erbium in a reverse nanofocusing waveguide - Güsken, Nicholas Alexander; Fu, Ming; Zapf, Maximilian; Nielsen, Michael P.; Dichtl, Paul; Röder, Robert; Clark, Alex S.; Maier, Stefan A.; Ronning, Carsten; Oulton, Rupert F. (Nature Communications)
Abstract Since Purcell’s seminal report 75 years ago, electromagnetic resonators have been used to control light-matter interactions to make brighter radiation sources and unleash unprecedented control over quantum states of light and matter. Indeed, optical resonators such as microcavities and plasmonic antennas offer excellent control but only over a limited spectral range. Strategies to mutually tune and match emission and resonator frequency are often required, which is intricate and precludes the possibility of enhancing multiple transitions simultaneously. In this letter, we report a strong radiative emission rate enhancement of Er 3+ -ions across the telecommunications C-band in a single plasmonic waveguide based on the Purcell effect. Our gap waveguide uses a reverse nanofocusing approach to efficiently enhance, extract and guide emission from the nanoscale to a photonic waveguide while keeping plasmonic losses at a minimum. Remarkably, the large and broadband Purcell enhancement allows us to resolve Stark-split electric dipole transitions, which are typically only observed under cryogenic conditions. Simultaneous radiative emission enhancement of multiple quantum states is of great interest for photonic quantum networks and on-chip data communications.

Methode zur Simulation des temperaturabhängigen Crashverhaltens von strukturellen Klebverbindungen - Striewe, Marius; Teutenberg, Dominik; Hein, David; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar (Klebtechnische Doktorandenseminare 2020 - 2022)

Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

Review on: Daniel Benedikt Stienen: Verkauftes Vaterland - Schönhärl, Korinna (Sehepunkte)

Review on: Sven Steinmo: Willing to Pay? A Reasonable Choice Approach - Schönhärl, Korinna (HSozKult)

Franz von Fürstenbergs Konzeption der Universität Münster als aufgeklärte Überbietung Paderborns - Süßmann, Johannes (Gründung und Aufbau der Universität Münster, 1773–1818. Zwischen katholischer Aufklärung, französischen Experimenten und preußischem Neuanfang)